Long-term outcomes and predictors of recurrence after pulmonary vein isolation with multielectrode ablation catheter in patients with atrial fibrillation. Issue 4 (April 2018) - Fredersdorf, Sabine; Fenzl, Carolin; Jungbauer, Carsten; Weber, Stefan; von Bary, Christian; Dietl, Alexander; Seegers, Joachim; Maier, Lars S.; Ücer, Ekrem
Abstract : Purpose: Despite various techniques used in atrial fibrillation ablation, recurrence of atrial arrhythmias still constitutes a clinical problem. The aim of this study was to document the long-term outcomes of pulmonary vein isolation with a ring-shaped ablation catheter (PVAC). Methods: All consecutive patients presenting with paroxysmal or persistent atrial fibrillation (pxAF or perAF, respectively) treated with PVAC (first generation) were enrolled. After standard follow-up during the first year, all patients were contacted for long-term follow-up. In addition to the patient's medical history, 3-day Holter monitoring was performed. Endpoints were atrial fibrillation-related symptoms, ECG documentation of atrial fibrillation or other left atrial arrhythmias and reablation. Results: In total, 125 patients (78% with pxAF) were enrolled. All but two pulmonary veins (0.4% of 485 pulmonary veins) could be successfully isolated. At 12 months, 83% of patients in the pxAF group and 53% of patients in the perAF group were free from symptoms. The mean long-term follow-up was 51 ± 14 months. Regarding long-term efficacy, 56% of patients in the pxAF group and 28% of patients in the perAF group were free from any recurrence at 72 months. Independent predictors of event-free survival were perAF (hazard ratio 2.76, P = 0.001) and the existence of mild valvular disease (hazard ratio 2.69, P = 0.001). No significant complication due to PVAC occurred, especially no ischemic stroke. Conclusion: Long-term follow-up indicated for the first time in such a considerable cohort that pulmonary vein isolation with PVAC is a safe and very efficient method for treating pxAF – despite known microembolism issues. Patients with perAF receive less benefit from PVAC and ablation therapy should be reserved to pxAF. Significantly, even mild valvular disease was an independent predictor of atrial fibrillation recurrence.